DISTRIBUTED SHARED MEMORY - Chaudhary, Vishal (IJRDO -Journal of Computer Science Engineering, 2015)
Distributed shared memory (DSM) systems have attracted considerable research efforts recently, since they combine the advantages of two different computer classes: shared memory multiprocessors and distributed systems. The most important one is the use of shared memory programming paradigm on physically distributed memories. In the first part of this paper, one possible classification taxonomy, which includes two basic criteria and a number of related characteristic, is proposed and described. According to the basic classification criteriaimplementation level of DSM mechanism--systems are organized into three groups: hardware, software, and hybrid DSM implementations. The second part of the paper represents an almost exhaustive survey of the existing solutions in an uniform manner, presenting their DSM mechanisms and issues of importance for various DSM systems and approaches. Software DSM systems can be implemented in an operating system (OS), or as a programming library and can be thought of as extensions of the underlying virtual memory architecture. When implemented in the OS, such systems are transparent to the developer; which means that the underlying distributed memory is completely hidden from the users